Indigenous Communication System in Kokana Tribes (Indian Journal of Extension Education, 2013)
The study was conducted in tribal villages from Surgana tehsil of Nasik District of Maharashtra state. The data were collected from 120 respondents. Majority of the Kokana tribes belonged to the age group of 45 years and above. More than th one-third (35.00 %) of the Kokana tribes were educated up to pre-primary level i.e. up to 4 standard. Maximum families of Kokana tribe’s had agriculture as main occupation and having annual income between ` 50,001/- to `1.00,000/-. Most of them possessed medium size of land holding i.e. up to 1.01 to 2.00 ha. They had nuclear family type and medium sized family i.e. 5 to 6 members. They had medium level of participation in any social organisation. Regarding indigenous communication systems cent per cent Kokana tribes knew about their traditional Kokana dance, and performed during the marriage ceremony.Cent per cent of them sang their traditional spiritual songs during Dongerdev festival, Avasar festival and Navratra festival for community, personal health and personal aim (Navas).Most of the Kokana tribe knows about the government schemes like Paryavaran Santulan Yojana, Village water Supply Scheme, Sarva ShikSha Abhiyan, Gaon Tanta Mukti Abhiayan, Jal Swaraj Prakalp, Watershed development programme, National Horticulture Mission, National Rural Health Mission and Zilla Parishad schemes which are running in the village.